Critical Care Management of Severe Acute Pancreatitis: Current Concepts, Clinical Challenges, and Future Perspectives - Sándor Márton (Life, 2026)
Acute pancreatitis is a common and heterogeneous inflammatory disorder whose clinical course ranges from a self-limited illness to persistent organ failure, infected pancreatic necrosis, and prolonged critical illness. Contemporary management has moved away from protocolised aggressive fluid loading, prolonged fasting, prophylactic antibiotics, and early open necrosectomy. Instead, current care emphasises repeated physiological assessment, moderate goal-directed resuscitation, early enteral or oral nutrition, organ-specific support, antimicrobial stewardship, and delayed minimally invasive intervention within a multidisciplinary step-up strategy. This narrative review examines acute pancreatitis from an intensive care perspective. Particular attention is given to early risk stratification, intensive care unit triage, haemodynamic and respiratory support, acute kidney injury, intra-abdominal hypertension, nutrition, biliary source control, diagnosis and treatment of infected necrosis, and the timing and selection of endoscopic, radiological, and surgical interventions. The implications of obesity, pregnancy, advanced age, and multimorbidity are also discussed. Recent randomised trials have clarified several clinically important questions: aggressive hydration increases fluid overload without improving outcomes; routine urgent endoscopic retrograde cholangiopancreatography is not beneficial in predicted severe biliary pancreatitis without cholangitis; postponed drainage may avoid invasive intervention in a substantial proportion of patients with infected necrosis; and endoscopic or minimally invasive approaches reduce treatment burden compared with primary open surgery. Persistent organ failure remains the principal determinant of mortality, while infected necrosis further increases risk and complexity. Future progress will depend on dynamic prediction models, biomarker-guided antimicrobial decisions, personalised haemodynamic strategies, phenotype-directed immunomodulation, and regionalised multidisciplinary care.